Case Report: A Frameshift Mutation in MSH2 Exon 2 in a Kidney Recipient With Muir–Torre Syndrome - Feng, Yifei; Feng, Jianqing; Bao, Jianrong (Frontiers in Oncology, 2021)
Muir-Torre syndrome (MTS), a rare subtype of Lynch syndrome, is mostly autosomal dominant, which is caused by germline mutations in DNA mismatch repair (MMR) genes, the resulting microsatellite instability (MSI) of which increases the risk of developing sebaceous and other visceral tumors. Several reports have showed an association between immunosuppressive agents and the progression of latent MTS. In this report, we described a 41-year-old man with a history of kidney transplantation, having a rapid growth of the nodule on the anterior chest under immunosuppressive therapy, which was histologically proved to be sebaceous carcinoma. Systemic evaluation for visceral malignancies revealed sigmoid adenocarcinoma. These findings were consistent with the clinical diagnosis of MTS. Histological findings showed an absence of MMR proteins, including MSH2 and MSH6 both in the sebaceous carcinoma and sigmoid adenocarcinoma on immunohistochemical (IHC) analysis. A frame-shift mutation of c.229_230delAG (p. Ser77fs) in the MSH2 exon 2 in the lesion was detected by next-generation sequencing (NGS) analysis. This case report not only reveals a new site of MSH2 mutation in this family of East Asian descent but also highlights the importance of adequate diagnosis for Muir–Torre syndrome, as well as further prevention of the development of latent visceral tumors in kidney transplant recipients.